Maternal consumption and perinatal exposure to non-nutritive sweeteners: should we be concerned? - Concha, Francisca; Sambra, Verónica; Cáceres, Paola; López-Arana, Sandra; Carvajal, Bielka; Gotteland, Martín (Frontiers in Pediatrics, 2023)
The context for this review is the rapid increase in the use of non-nutritive sweeteners (NNSs) instead of sugar in foods and beverages, a situation so prevalent in some countries that consumers are finding it increasingly challenging to access foods without NNSs. The benefits of consuming NNSs on obesity and diabetes are now being questioned, and studies have shown that they may exert physiological activities, sometimes independently of sweet taste receptor stimulation. Few studies, limited mainly to North American and European countries, have described the consumption of NNSs by pregnant or lactating women and infants. Most focus on beverages rather than foods, but all agree that consumption levels have increased dramatically. Although some studies report a negative impact of NNSs on the risk of preterm birth, increased birth weight and decreased gestational age, the level of evidence is low. Several studies have also reported increased weight gain in infancy, associated with maternal NNS intake. Interestingly, several NNSs have been detected in amniotic fluid and breast milk, usually (but not always) at concentrations below their established detection limit in humans. Unfortunately, the impact of chronic exposure of the fetus/infant to low levels of multiple NNSs is unknown. In conclusion, there is a stark contrast between the galloping increase in the consumption of NNSs and the small number of studies evaluating their impact in at-risk groups such as pregnant and lactating women and infants. Clearly, more studies are needed, especially in Latin America and Asia, to fill these gaps and update recommendations.